SISTEM ONLINE ADMINISTRASI KURIKULUM SEBAGAI SOLUSI PERBAIKAN LAYANAN ADMINISTRASI DI SMA NAHDLATUL ULAMA 1 GRESIK - admin admin; Haniatun Masluroh (DIDAKTIKA, 2013)
Administration and Data Processing curriculum at SMA NU 1 Gresik lessons are done by teachers. After the data is processed, the parents and students are right to know: a) Preparation of annual, semiannual, monthly and weekly work plans; b) Adjustment timetable c) Preparation of the test and the exam schedule d) Preparation of a list of books and tool lessons that will be used in activities for increasing student achievement; e) Preparation of appraisal norms, f) Record and report the results of activities of student achievement; g) Preparation of schedules and plan learning activities in the classroom and outside the classroom. The data is obtained by dividing the paperwork that must be made by the number of teachers' lesson without coordination or discussion made in detail made by the teacher so that there is the possibility of dissentients. By improving the manufacturing system administration curriculum using online, it will have a major impact on the quality of graduates. If the quality of graduates according to the expectations of parents, the community and users of the graduates of customer satisfaction will also increase so that the school will gain great confidence of the public and users of the various elements of graduates.